PEMANFAATAN AMPAS TEBU UNTUK MENINGKATKAN KUALITAS (SIFAT ORGANOLEPTIK, PARAMETER OKSIDASI, DAN PROFIL ASAM LEMAK) PADA MINYAK JELANTAH - Wahyuni, Winda Tri; Srimiati, Mia (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2017)
Used cooking oil is widely used by Indonesian people to fry many foods, which is the oil have been oxidized. On the other hand, Indonesia has a lot of unutilized waste products, such as bagasse. The design of the study was experimental, which added the bagasse to the used cooking oil to filtrate the physical and chemical impurities. There were 3 kinds of treatments, i.e. F1 (3% of bagasse), F2 (5% bagasse), F3 (7% bagasse), and control (without bagasse). The characteristics of used cooking oil (control) were: dark brown, rancid odor, having 0,39% of free fatty acid, 12,39 meq/Kg of peroxide value, 35,52% w/w palmitic acid, 35,31 oleic acid, 9,35% w/w linoleic acid, and 3,32% w/w stearic acid. The best treatment taken on the highest yield, organoleptic test, and peroxide number was F1 (3% bagasse), it could reduced free fatty acid and peroxide value become 0,26% and 6,67 mEq/kg. The number of fatty acids from the best treatment were dominated by palmitic acid (33,94% w/w), oleic acid (33,92% w/w), linoleic acid (9,03% w/w) and also had stearic acid (3,21% w/w). The bagasse can significantly reduce the organoleptic properties, the oxidation parameters, and other fatty acids of used oil (P<0,05). So, the bagasse could potentially decrease the oxidation parameters of used cooking oil.